Incidence of tax evasion in public policies to combat poverty. - Grajeda Grajeda , Rebeca Patricia (Posgrados de la División de Ciencias Económica Administrativas, 2021)
This article addresses the issue of tax evasion as a factor that impacts on the State's collection efficiency and the consequences that this phenomenon has on the public treasury, by limiting the resources that could be allocated to promoting public policies and social programs that improve social equity and reduce income inequality.   Through an approach to research that reveals poverty rates in Latin American countries, tax evasion is identified as one of the factors that promote the low effect of the redistributive role of the State, coupled with a low tax pressure with regressive characteristics and orientation. inadequate public spending. Through a theoretical analysis based on documentary information, the methodologies applied in the quantification of this phenomenon are proposed that allow governments to have parameters and evaluate the efficiency when collecting, in order to plan the audit and carry out the modification of tax legislation, always seeking equity in the payment of taxes.